LEARNING INNOVATION USING WORDWALL WEBSITE APPLICATION - Hasibullah, Muhammad Umar (FKDP (Forum Komunikasi Dosen Peneliti), 2023)
This study aims to describe the innovation of lecture technology advances in PAI subjects during the implementation of distance learning to improve learning outcomes. Students from low to high, so that the full achievement of lecture goals. This research uses a type of library material-based literature research as a source of information to answer problems related to innovation in lecture technology advances by using a web-based word wall application on PAI subjects during the implementation of distance lectures. Creating innovative technological advances in lecturer lectures that increase the understanding of knowledge, attitudes, and skills of each student. The use of a Website-based Wordwall Application is the best solution to provide a deep understanding and study Islamic Religious Education lessons thoroughly. The website-based Wordwall application also has an important role in lectures and is able to associate feelings of fun and not pressured in doing questions or exercises in the lecture process. In addition, the website-based wordwall application is also able to form collective knowledge for students, increasing student motivation in doing assignments.